STUDY OF RECOVERY ON GRIND SIZE RELANTIONSHIP USING BAZIN METHODOLOGY IN MECHANICAL SCAVENGER FLOTATION AT NORTH CONCENTRATOR PT FREEPORT INDONESIA - Adelia Ardiyana Putri, Made
PT Freeport Indonesia (PTFI) is a subsidiary of Freeport-McMoRan Copper & Gold Inc. (FCX) operating in Papua. The North concentrator (C1) was built in 1972 with a capacity of 31,700 tons per day. According to the trend of existing data, the copper and gold recovery from the north concentrator has a low value when compared with other concentrators. Particle size is very influential on the recovery of the flotation process because it is closely related to the liberation rate of the particles. In the mechanical scavenger, the relationship between grind size and recovery is unknown, so a Bazin analysis is needed to produce an optimum flotation process in the mechanical scavenger. Bazin methodology is a modeling of recovery at a certain grind size. The first steps carried out in this project were pre-sampling and continued with sampling of the feed, concentrate and tailings streams from the mechanical scavenger. The tests carried out aim to obtain data, which are the copper and gold content of each stream, X-Ray Diffraction (XRD) of each stream, particle size distribution (PSD), and gold and copper content in each size distribution. The sample preparation process was carried out at the Metallurgical Laboratory, by separating the samples to be tested to represent each stream (bulk) and those to be tested to determine PSD. In the bulk sample, filter press, drying, pulverized, and splitting were carried out for XRD testing and content in the Quality Control Laboratory. Then the samples that will be tested to determine PSD are carried out wet screen, filter press, drying, and dry screen. In the dry screen process, 8 screen sizes are used, namely 100 #, 150 #, 200 #, 270 #, 325 #, 400 #, 500 #, and 635 #. Samples of each size distribution will be weighed and pulverized for assay testing at the Quality Control Laboratory. The size distribution in the feed is extremely fine. This is evidenced by the P80 value of the feed is 57.59 ?m with a %-Cumulative Passing Weight at size 25.4 ?m is 51.25%. It is known that the %-Cumulative Passing Weight of 51.25% still contains 52.61% Cumulative Cu and %-Cumulative Passing Weight of 48.31% still contains 39.12% Cumulative Au. In the calculation of recovery by size and recovery on size using the Bazin methodology, it is found that by changing the particles to be coarser, it can increase the recovery of mechanical scavenger flotation. The optimum P80 value in the flotation process is estimated at 67 ?m with a recovery value of 85.17% for copper and 65.99% for gold. Increasing the P80 value from 57.59 ?m to 67 ?m will reduce revenue loss by $189,661,172 per year.